2019
DOI: 10.1055/s-0039-1688414
|View full text |Cite
|
Sign up to set email alerts
|

HAEMOcare: The First International Epidemiological Study Measuring Burden of Hemophilia in Developing Countries

Abstract: Introduction Optimizing hemophilia care remains challenging in developing countries. Burden-of-disease studies are important to develop strategies for improving hemophilia care. Aim The HAEMOcare study evaluated the factors contributing to hemophilia-related orthopedic disease burden in developing countries. Methods HAEMOcare was a noninterventional, cross-sectional, epidemiological study conducted in Algeria, India, Morocco, Oman, and South Africa. Male patients with severe hemophilia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
1
16
0
2
Order By: Relevance
“…In that study, 70% of patients being treated on-demand reported limitations on the Hemophilia Joint Health Score (HJHS) from haemophilia-related orthopaedic morbidities. 3 In a study conducted in Algeria, 61% of patients required surgical intervention due to joint disease and the majority of the surgical intervention was carried out before 30 years of age. 14% of the overall surgeries were joint replacement surgeries with the youngest patient being 11 years of age.…”
Section: Arthroplasty In Haemophilia: Double-edged Sword In Low/ Middmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, 70% of patients being treated on-demand reported limitations on the Hemophilia Joint Health Score (HJHS) from haemophilia-related orthopaedic morbidities. 3 In a study conducted in Algeria, 61% of patients required surgical intervention due to joint disease and the majority of the surgical intervention was carried out before 30 years of age. 14% of the overall surgeries were joint replacement surgeries with the youngest patient being 11 years of age.…”
Section: Arthroplasty In Haemophilia: Double-edged Sword In Low/ Middmentioning
confidence: 99%
“…The HAEMOcare study conducted in five developing countries reported 84% of patients had target joints with a mean annual bleeding rate of 26%, which is significantly higher compared to developed countries. In that study, 70% of patients being treated on‐demand reported limitations on the Hemophilia Joint Health Score (HJHS) from haemophilia‐related orthopaedic morbidities 3 . In a study conducted in Algeria, 61% of patients required surgical intervention due to joint disease and the majority of the surgical intervention was carried out before 30 years of age.…”
mentioning
confidence: 99%
“…Therefore, we must carefully check and confirm the validity of the KK regularization by calculating the KK corrections with another regularization method. In order to avoid the above ambiguity of the KK regularization, we regularize the 4-momentum integrals by the method of dimensional regularization before summing all the KK states, following the paper [36]. Now, we define the proper time integral I n as follows:…”
Section: B Casimir Corrections For the Higgs Mass With Dimensional Rmentioning
confidence: 99%
“…Optimal management for people with severe haemophilia involves prophylaxis with regular infusions of FVIII or FIX, which helps to reduce the risk of bleeds and joint damage [3] . However, this is expensive and frequently not an option in economically developing countries, where people with haemophilia (PwH) more commonly receive on-demand treatment with factor replacement only when bleeding occurs [4][5] . Children and adults with mild or moderate haemophilia also receive on-demand treatment.…”
mentioning
confidence: 99%